A Systematic Approach for Developing Decision Aids: From Cognitive Work Analysis to Prototype Design and Development. Issue 2 (23rd May 2016) - Dhukaram, Anandhi Vivekanandan; Baber, Chris
ABSTRACT: Cognitive Work Analysis (CWA) has proved successful in supporting Human Factors analysis, providing a system‐level view of operations that can be used to understand how systems achieve their missions. However, a critical gap exists in the transition from CWA to prototype design and implementation. The aim of this paper is to fill this gap between CWA and implementation. This paper describes an approach for the design of software system in which CWA descriptions are converted to Unified Modeling Language (UML) models. The approach presented in this paper is intended to be minimalistic and streamlined, to focus on the design of a prototype. Following the design process, a Decision Aid prototype was developed. This prototype is evaluated against the original CWA to check that the translation has been effective. This paper shows how CWA can be integrated with UML for prototype design and implementation. We believe that this paper should prove useful to a range of practitioners concerned about maintaining a user's cognitive perspective during specification and analysis of a system.